The Effect Of Corporate Governance And Political Connections On The Application Of Conditional Conservatism (Study On Non-Financial Companies Registered In Indonesian Stock Exchange In 2012-2018) - Herawansyah, Herawansyah; Indriani, Rini; Sitorus, Nadine Nathasya (Disclosure: Journal of Accounting and Finance, 2021)
This study aimed to examine the effect of corporate governance and political connections on the application of conditional conservatism. The sample in this study are non-financial companies listed on Indonesia Stock Exchange period 2012-2018. The number of samples in this study were 82 non-financial companies. Data analysis was performed with multiple regression analysis. The result of study showed that board of commissioner, audit committee size, audit committee independence, and institutional ownership have an effect on conditional conservatism. This study also has a result that political connections have a negatif influence on conditional conservatism. It means more higher the companies have indicated by political connections, the lower the application of conditional conservatism. Variable board of director, independence commissioner, auditor expertise, the quality of the accounting firm which is proxied by BIG4, and managerial ownership have no effect on conditional conservatism.